Desempenho acadêmico no ensino superior: uma análise contextual - Carneiro, Luci Annee Vargas (2017)
In the last decade, a set of public policies for expanding access to higher education has taken place in Brazil, culminating in a significant increase in vacancies public and private in institutions reaching a public previously excluded from this stage of education. Current research indicates that the academic course in Higher Education for many students is marked by difficulties and barriers that end up limiting academic potential. The dissertation presented here describes and analyzes the academic performance indexes of the Federal University of Pampa - Campus Alegrete in the academic years of 2015 and 2016. The general objective of this study is to analyze evasion and retention indexes, aiming at surveying strategies to overcome this problem. The qualitative methodology is based on a documental analysis of institutional data obtained in the information systems of the University and in the Pedagogical Projects of the graduation courses of the Campus. The academic achievement indexes expressed in this study demonstrate high retention rates in basic curricular components common to the courses, evasion accentuated in the first year of graduation and low academic performance of entrants. The results point to great challenges in coping with the phenomena of retention and evasion, as well as in overcoming the learning difficulties experienced by students, especially the entrants. The conclusions point to the collective need to rethink curricular and pedagogical practices in the Campus.